Assessing cadmium exposure risks of vegetables with plant uptake factor and soil property. (July 2018) - Yang, Yang; Chang, Andrew C.; Wang, Meie; Chen, Weiping; Peng, Chi
Abstract: Plant uptake factors (PUFs) are of great importance in human cadmium (Cd) exposure risk assessment while it has been often treated in a generic way. We collected 1077 pairs of vegetable-soil samples from production fields to characterize Cd PUFs and demonstrated their utility in assessing Cd exposure risks to consumers of locally grown vegetables. The Cd PUFs varied with plant species and pH and organic matter content of soils. Once normalized PUFs against soil parameters, the PUFs distributions were log-normal in nature. In this manner, the PUFs were represented by definable probability distributions instead of a deterministic figure. The Cd exposure risks were then assessed using the normalized PUF based on the Monte Carlo simulation algorithm. Factors affecting the extent of Cd exposures were isolated through sensitivity analyses. Normalized PUF would illustrate the outcomes for uncontaminated and slightly contaminated soils. Among the vegetables, lettuce was potentially hazardous for residents due to its high Cd accumulation but low Zn concentration. To protect 95% of the lettuce production from causing excessive Cd exposure risks, pH of soils needed to be 5.9 and above. Graphical abstract: Image 1 Highlights: Vegetable PUFs of Cd are probabilistic in nature and follow log-normal distributions. The site- and soil property-normalized PUF reduces the uncertainty in exposure assessment. Improved soil pH to 5.9 and above help protect 95% of the lettuce harvests from causing risky dietary Cd exposures. Abstract : The site- and soil property-normalized plant uptake factor reduced uncertainties in estimating the cadmium exposures due to consumptions of locally grown vegetables.